On the Influence of Kinetic Uncertainties on the Accuracy of Numerical Modeling of an Industrial Flameless Furnace Fired With NH3/H2 Blends: A Numerical and Experimental Study - Ferrarotti, Marco; Bertolino, Andrea; Amaduzzi, Ruggero; Parente, Alessandro (Frontiers in Energy Research, 2020)
Ammonia/hydrogen-fueled combustion represents a very promising solution for the energy scenario to come. This study aims to shed light and understand the behaviour of ammonia/hydrogen blends under flameless conditions. A first-of-its-kind experimental campaign was conducted to test fuel-flexibility for different ammonia/hydrogen blends in a flameless burner, varying the air injector and the equivalence ratio. NO emissions increased drastically after injecting a small amount of NH3 in pure hydrogen (10% in volume). An optimum trade-off between NOx emission and ammonia slip was found when working sufficiently close to stoichiometric conditions ( = 0.95). In general, a larger air injector (ID25) reduces emissions, especially at = 0.8. A well-stirred reactor (WSR) network with exhausts recirculation was developed exchanging information with CFD simulations, to model chemistry in diluted conditions. Such a simplified system was then used in two ways: (i) to explain the experimental trends of NOx emissions varying the ammonia molar fraction within the fuel blend, (ii) to perform an uncertainty quantification study. A sensitivity study coupled with Latin Hypercube Sampling (LHS) was used to evaluate the impact of kinetic uncertainties on NOx prediction in the WSR network model. The influence of the identified uncertainties was then tested in more complex numerical models, such as RANS simulations of the furnace. The major over-predictions of existing kinetic scheme was 19 then alleviated significantly, confirming the crucial role of a well-characterized detailed kinetic mechanism for the accuracy of predictive numerical models for NH3/H2 mixtures in flameless regime.